Wireless access flexibility : First International Workshop, WiFlex 2013, Kaliningrad, Russia, September 4-6, 2013. Proceedings - Lyakhov, Andrey; Khorov, Evgeny; Bianchi, Giuseppe (Lecture notes in computer science, 2013)
This book constitutes the refereed proceedings of the First International Workshop on Wireless Access Flexibility, WiFlex 2013, held in Kaliningrad, Russia, in September 2013. The 13 full papers presented were carefully reviewed and selected for inclusion in this volume. The papers describe the latest results and novel research ideas in the field of flexible wireless access architecture design opening the door for innovative solutions significantly improving network performance. The following topics are covered in this volume: 4G and beyond, local area networks, multi-hop networks, sensor networks.